Indagation of serum and salivary reactive oxygen metabolite and cortisol levels in chronic periodontitis and stress-induced chronic periodontitis patients - Uma Sudhakar; Ramakrishnan Thyagarajan; Bhagyameena Jeyapal; Sushuruthi Jagadeesh; Parvathee Jayakumar (Wolters Kluwer Medknow Publications, 2017)
Background: Periodontal disease is not a conventional bacterial infection but is an inflammatory disease initiated by immune response against a group of microorganisms in susceptible hosts. There are many intriguing researches that unfold the secrets of chronic periodontitis. The current researches in chronic periodontitis are directed toward an approach that respects the scientific relationship between the various risk factors, the genetic factors, and the progression of the disease. Aim: This study aims to evaluate the cortisol and reactive oxygen metabolites (ROM) concentration in serum and to find out their association in periodontal health and disease. Materials and Methods: In this study, totally thirty patients have been taken and divided into two groups of chronic periodontitis (Group I) and stress-induced chronic periodontitis (Group II) and evaluated the correlation between the ROM and cortisol levels in them. This is the first study, where both the levels of ROM and cortisol are checked in the serum and saliva. The analysis is done to check the association between them. Statistical Analysis: The data were statistically analyzed using software program (SPSSV 16), Pearson correlation, and paired t-test. Results: Comparison of the mean ROM levels in Group I and Group II showed that mean ROM level in Group II is highly significant than Group I. Conclusion: Our study suggests that stress can have a role in the progression of periodontal disease by increasing the cortisol and ROM levels.